Google Sites Based E-book to Improve Mathematical Connectivity Skills in Probability - Heny Wijaya; Heni Pujiastuti (Universitas Suryakancana, 2026)
This study aims to develop a Google Sites-based e-book to improve high school students’ mathematical reasoning skills in probability. This study employs the Research and Development (R&D) method using the ADDIE model, which consists of the analysis, design, development, implementation, and evaluation stages. The research subjects included 40 11th-grade science students to measure the effectiveness of the media, 17 students to assess the practicality of the media, and 3 expert validators consisting of a media expert, a language expert, and a subject matter expert. Data collection techniques were conducted through validation sheets, student response questionnaires, and pretest and posttest assessments. The research results showed that the media received a validation percentage of 86.15% from the media expert, 89.23% from the language expert, and 93.33% from the content expert, all falling into the “highly suitable” category. The effectiveness test results showed that the average pretest score of 59.18 increased to 88.51 on the posttest, with an N-Gain value of 0.72 in the “high” category. Additionally, the classical mastery rate reached 93.33%, and the questionnaire results indicated that the medium falls into the practical category. Thus, the Google Sites-based e-book is deemed suiTabel, practical, and effective for enhancing students’ mathematical connection skills in probability material.